2003
DOI: 10.4049/jimmunol.170.6.3263
|View full text |Cite
|
Sign up to set email alerts
|

Activation of STAT3 by IL-6 and IL-10 in Primary Human Macrophages Is Differentially Modulated by Suppressor of Cytokine Signaling 3

Abstract: On human macrophages IL-10 acts as a more potent anti-inflammatory cytokine than IL-6, although both cytokines signal mainly via activation of the transcription factor STAT3. In this study we compare IL-10 and IL-6 signaling in primary human macrophages derived from blood monocytes. Pretreatment of macrophages with PMA or the proinflammatory mediators LPS and TNF-␣ blocks IL-6-induced STAT3 activation, whereas IL-10-induced activation of STAT3 remains largely unaffected. Although LPS induces the feedback inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
257
2
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(276 citation statements)
references
References 52 publications
(66 reference statements)
14
257
2
3
Order By: Relevance
“…In contrast, in our experiments, Stat3 function was suppressed, possibly secondary to heterodimerization with high levels of activated Stat1, but levels of Stat3 tyrosine phosphorylation were preserved. The intact activation of Jak1 and Stat3 by IL-10 in IFN-␥-activated macrophages is consistent with previous reports showing that IL-10 signaling can be relatively resistant to inhibition by SOCS proteins in a cell type-dependent manner (37,38). Our results showing that IFN-␥ regulates the balance of Stat1 and Stat3 activation by IL-10, together with the results from Biron and O'Shea and colleagues (36) demonstrating differential activation of Stat1 and Stat4 by IFN-␣␤ over the time course of a viral infection in vivo, support the notion that dynamic regulation of the activation of different STATs by cytokines plays an important role in determining the activity of pleiotropic cytokines.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, in our experiments, Stat3 function was suppressed, possibly secondary to heterodimerization with high levels of activated Stat1, but levels of Stat3 tyrosine phosphorylation were preserved. The intact activation of Jak1 and Stat3 by IL-10 in IFN-␥-activated macrophages is consistent with previous reports showing that IL-10 signaling can be relatively resistant to inhibition by SOCS proteins in a cell type-dependent manner (37,38). Our results showing that IFN-␥ regulates the balance of Stat1 and Stat3 activation by IL-10, together with the results from Biron and O'Shea and colleagues (36) demonstrating differential activation of Stat1 and Stat4 by IFN-␣␤ over the time course of a viral infection in vivo, support the notion that dynamic regulation of the activation of different STATs by cytokines plays an important role in determining the activity of pleiotropic cytokines.…”
Section: Discussionsupporting
confidence: 78%
“…Thus, it is possible that the PGE 2 -induced inhibition of IL-6 signaling might be due to de novo synthesis of SOCS3. In our studies, IL-10-induced STAT3 phosphorylation was not affected by PGE 2 -mediated induction of SOCS3, which is consistent with another report suggesting that IL-10-induced STAT3 activation is much less sensitive to the inhibitory activity of SOCS3 (25).…”
Section: Modulation Of Cytokine-induced Stat3 Phosphorylation Is Depesupporting
confidence: 80%
“…Because SOCS3 is a major feedback inhibitor of IL-6-induced STAT signaling (20,24,25), we suspected that SOCS3 may be involved in the PGE 2 -mediated inhibition of IL-6-induced STAT3 activation. PGE 2 rapidly induced SOCS3 mRNA expression within 30 min (Fig.…”
Section: Modulation Of Cytokine-induced Stat3 Phosphorylation Is Depementioning
confidence: 99%
“…Support for this concept comes from STAT3 DNA binding studies performed in the presence of proinflammatory stimuli. These studies found that the initial STAT3 activated by the IL-6R in the presence of TLR4 or IL-1R signaling caused a block in DNA binding activity of STAT3 that was not observed when STAT3 was activated by the IL-10R (42)(43)(44). Therefore, it is possible that STAT3 located in the environment of gp130 is subject to additional modifications that inhibit STAT3 function.…”
Section: Different Types Of Stat3 Signalsmentioning
confidence: 99%